THE USE OF COMIC STRIPS IN TEACHING READING A DESCRIPTIVE TEXTAT THE SEVENTH GRADE STUDENTS OF SMPN 3 PEKANBARU - Syaifullah Syaifullah (Lectura : Jurnal Pendidikan, 2014)
This study is about the use of comic in teaching a descriptive text becausemost of the students at the seventh grade of SMPN 3 Pekanbaru got some problem incomprehending the text. The main objective of this study was to find out whether thestudents taught reading a descriptive text using comic strips achieve better than thosewho do not taught reading using comic strips at the seventh grade students of SMPN3 Pekanbaru. The design of the research was experimental study. The researcher gavetry-out test to analyze validity and reliability of each item. Some test was used toanalyze the data that obtained from the pre-and post-test. They were normality test,Homogeneity test, and t-test. It was showed that the mean of experimental score washigher than the mean of control class (74.51>64.75). The test of hypothesis using ttestformula showed the value of the Asym Sig (2-tailed) 0.000 < 0.05. The nullhypothesis was rejected. Then, the criteria value of N-gain pre-test and post testexperimental class was middle. In conclusion, students who taught reading adescriptive text with comic strips achieved better than students who did not taughtwithout comic strips.